Drafting of the Union treaty in September-December 1991: from the dismantling of statehood to the USSR's collapse - A. V. Lukashin (Управление)
The article is devoted to the consideration of internal political processes in the Soviet Union at the final stage of its existence, in particular, the political struggle between the President of the USSR M.S. Gorbachev and Republican leaders in the course of the preparation of the draft Union Treaty in the autumn of 1991 («Novo-Ogarevo-2»). The task of the research is to reconstruct the process of preparation of the draft Union Treaty in September-November 1991, its discussions during the meetings of the State Council of the USSR, and to assess the role of this Treaty in the dismantling of the USSR`s political system. The main source of this research was the verbatim records of the State Council`s meetings, numerous comments and additions to the autumn draft of the Union Treaty, which are stored in the archive Gorbachev Foundation. On the basis of these archival documents, as well as press materials, documentary collections, memories of eyewitnesses of those events, the author compares the positions of the Union and the Republican leaders on the structure of the future Union of the USSR: membership in the updated Union, the tax system, state bodies, the legal system. The key problem, to which all discussions of the Union Treaty were reduced, concerned distribution of power between the Union and Republican elites. The analysis of the sources allows us to conclude that during the autumn negotiations a compromise between the Union and the Republican leaders was impossible - the project “Novo-Ogarevo-2” was doomed to failure initially. If M.S. Gorbachev made attempts to legally secure the preservation of the Union in the form of a confederation, the Republican leaders, first of all, the President of Russia B.N. Yeltsin, based on the adopted Declaration of sovereignty, sought independence and separation from the USSR. The Union Treaty, originally designed to create the necessary balance in the relations between the Center and the republics, in practice was an instrument for the implementation of the ambitions of the Republican elites and became one of the factors of the USSR`s collapse.